The Social Skills of Homeschooler: A Case Study Exploring the Perception of Religiously Minded Muslim Parents in Jakarta - Syahril Budiman Bahri; Dawood Abdulmalek Yahya Al-Hidabi; Nik Md. Saiful Azizi Nik Abdullah; Betania Kartika (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2024)
The issue of social skills is always at the centre of the homeschooling discussion. Many studies have been carried out on homeschooled children’s social skills, but very little research has attempted to explore homeschooled children’s social skills from the perspective of both the homeschooling father and the homeschooling mother, especially those who are religiously minded Muslims. This paper highlighted the perspectives of religiously minded Muslim homeschooling parents on their children’s social skills. The researchers used a case study approach in a qualitative research design. A homeschooling father and a homeschooling mother were both purposefully chosen as informants. Individual interviews were conducted with both informants. To analyse the data, the researchers employed thematic analysis. Several themes emerged from the research. The findings revealed that the social skills of homeschooled children are the capacity to adapt to society, the ability to establish relationships, and the competence to manage disagreements. Moreover, the goal of social skills is to build harmony by achieving Allah's pleasure, followed by gaining people's pleasure.